A study of atmospheric pollutants (particulates, metallic elements) at an agricultural site. Issue 1 (3rd April 2021) - Fang, Guor-Cheng; Kao, Chao-Lang; Ni, Sheng-Chung; Chen, Yi-Hsiu
Abstract: In this study, the total suspended particulate (TSP) concentrations and dry deposition of ambient air particulates are measured using a high-volume air sampler and a dry deposition plate at an agricultural sampling site in central Taiwan from March of 2019 to February of 2020. In addition, the concentrations of metallic elements attached to the particulates and dry deposits are analyzed using inductively coupled plasma atomic emission spectroscopy (ICP-AES). Finally, the TSP and metallic elements concentrations in TSP at different sampling sites around the world are also compared and discussed. The results indicated that the average highest TSP concentrations and dry depositions values both occurred in autumn, and the agricultural sampling site had the average greatest ambient air particulates dry depositions velocities when compared with other previous characteristic-related studies in Taiwan. In addition, metallic element Al had the average highest concentrations and dry depositions and metallic element Cd had the average lowest concentrations and dry depositions values in this study. In addition, metallic elements Cr, Cu, Pb, and Zn had the average highest concentrations when compared with other typical sampling site studies (airport, suburban, downtown, residential, industrial, and wetlands) in central Taiwan. Furthermore, when compared with the other previous metallic elements concentrations found in related studies in other regions from 1978 to 2020, the results obtained in this study indicated that the average metallic element concentrations Cr, Cu, Pb, and Zn in Taiwan were only lower than those reported in India and China. Taiping District is the main fruits production area in central Taiwan. Therefore, continued monitoring of ambient air related pollutants and finding the possible pollution sources have become an important issue for this agricultural site. From the above analysis, we also conclude that ambient air particulates and all the metallic elements dry deposition values obtained in this study were higher than those from the other characteristic sampling sites where studies were previously conducted in Taiwan.